Clinical reasoning strategies used during care planning. - Fowler LP (Clinical Nursing Research)
This descriptive study provides insight into home health nurses' thinking processes as they planned care for chronically ill clients. The author interviewed five experienced home health nurses to elicit think-aloud data about 10 different chronically ill clients, obtaining 20 interviews. The researcher used verbal protocol analysis, a content analysis interpretive strategy, to unravel the concepts and label the cognitive processes used in the thinking task of planning nursing care. The following cognitive strategies were discovered: hypothesizing, cue logic, framing, reflexive comparison, prototype case reasoning, and testing. Findings support the importance of content, clinical context, and experience whenever reasoning to plan care. Findings did not support problem-solving models of thinking such as the nursing process. The findings for this study are applicable to staff development and education programs. Theoretical models of clinical reasoning need to be further developed and tested.